A study of Idioms denoting family In english and vietnamese (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This paper is to study semantic and syntactic features of English and Vietnamese idioms denoting family. Both qualitative and quantitative analysis is made us of investigation 462 idioms in English and Vietnamese together with numerous number of samples from dictionaries, short stories, novels, newspapers and from internet. The findings show that idioms denoting family have remarkable syntactic and semantic features and that there are some similarities and differences in some features. Causes are also dealt with the implications for the teaching and learning of idioms as well as for further study are put forward.